(Ⅰ)∵=(x2,y-cx),=(1,x+b),∥∴x2(x+b)=y-cx,
∴f(x)=x3+bx2+cx,f′(x)=3x2+2bx+c,
∴F(x)=f(x)+af′(x)=x3+(3a+b)x2+(2b+c)x+ac 为奇函数
∴F(-x)=-F(x),∴3a+b=0,ac=0,而a>0,
∴=-3,c=0.
(Ⅱ)由(Ⅰ)可知f(x)=x3-3ax2,f′(x)=3x2-6ax=3x(x-2a),
由f′(x)<0,得0<x<2a,故f(x)的单调递减区间为[0,2a],
若函数f(x)在[,a2]上单调递减,则[,a2]⊆[0,2a],⇔⇔<a<2,
而由(Ⅰ)知b=-3a,故-6<b<-.
(Ⅲ)当a=2时,由(Ⅰ)知b=-6,∴f(x)=x3-6x2,f′(x)=3x2-12x.
曲线y=f(x)在点A(t,f(t))处的切线方程为y-f(t)=f′(x)(x-t),其中f′(x)=3t2-12t.
联立y=f(x)与y-f(t)=f′(x)(x-t),得 f(x)-f(t)=f′(x)(x-t),
∴x3-6x2-t3+6t2 =(3t2-12t)(x-t),∴(x3-t3)-6(x2-t2)-(3t2-12t)(x-t)=0,
∴(x-t)(x2+tx+t2-6x-6t-3t2+12t)=0,∴(x-t)[x2+(t-6)x-t(2t-6)]=0,
∴(x-t)2(x+2t-6)=0
则x=t或x=-2t+6,而A,B不重合,则m=-2t+6,
S(t)=|m-t|•|f(m)-f(t)|=|6-3t|•|(6-2t)3-6(6-2t)2-t3+6t2|
=|6-3t|•|-9t3+54t2-72t|=|t-2|•|t(t-2)(t-4)|=t(t-2)2(4-t),
其中t∈(0,2)∪(2,4).
记kPD =g(t)==-t(t-2)2 =-(t3-4t2+4t),
∴g′(t)=-(3t2-8t+4)=-(3t-2)(t-2),t∈(0,2)∪(2,4).
列表如下:
t | (0,) | | (,2) | 2 | (2,4) |
g′(t) | - | 0 | + | 0 | - |
g(t) | ↘ | 极小值 | ↗ | 极大值 | ↘ |
又g(0)=0,g(
)=-16,g(2)=0,g(4)=-216,
由表可知:-216<g(t)≤0,即-216<kPD≤0.